Induction therapy with cetuximab plus docetaxel, cisplatin, and 5‐fluorouracil (ETPF) in patients with resectable nonmetastatic stage III or IV squamous cell carcinoma of the oropharynx. A GERCOR phase II ECHO‐07 study. (14th February 2015) - Chibaudel, Benoist; Lacave, Roger; Lefevre, Marine; Soussan, Patrick; Antoine, Martine; Périé, Sophie; Belloc, Jean‐Baptiste; Banal, Alain; Albert, Sébastien; Chabolle, Frédéric; Céruse, Philippe; Baril, Philippe; et al.
<x xml:space="preserve">Abstract</x> This phase II study reports a clinical and radiological complete response of 22% and a primary tumor overall response rate of 58% for ETPF in patients with moderately advanced squamous cell carcinoma of the oropharynx. The schedule of ETPF evaluated in this study cannot be recommended at this dosage.